Understanding Synaptogenesis and Functional Connectome in C. elegans by Imaging Technology - Hong, Jung-Hwa; Park, Mikyoung (Frontiers in Synaptic Neuroscience, 2016)
Formation of functional synapses is a fundamental process for establishing neural circuits and ultimately for expressing complex behavior. Extensive research has interrogated how such functional synapses are formed and how synapse formation contributes to the generation of neural circuitry and behavior. The nervous system of Caenorhabditis elegans, due to its relatively simple structure, the transparent body, and tractable genetic system, has been adapted as an excellent model to investigate synapses and the functional connectome. Advances in imaging technology together with the improvement of genetically encoded molecular tools enabled us to visualize synapses and neural circuits of the animal model, which provide insights into our understanding of molecules and their signaling pathways that mediate synapse formation and neuronal network modulation. Here we review synaptogenesis in active zones and the mapping of local connectome in C. elegans nervous system whose understandings have been extended by the advances in imaging technology along with the genetic molecular tools.